2016
DOI: 10.1007/s12205-016-0130-4
|View full text |Cite
|
Sign up to set email alerts
|

Application of sulphoaluminate cement to repair deteriorated concrete members in chloride ion rich environment-A basic experimental investigation of durability properties

Abstract: This paper presents a basic experimental investigation of the durability properties of Sulphoaluminate cement concrete (SACC) and Portland Cement Concrete (PCC). It is to discuss the potential application of Sulphoaluminate cement towards the repair of deteriorated concrete members in chloride ion-rich environment such as coastal engineering, using a SACC repair layer with higher strength than original damaged concrete. The chloride-related durability properties of SACCs were comprehensively studied through so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…The protection provided by Al(OH) 4 โˆ’ is attributed to its ability to release hydroxyl. In the corrosion process, localized acidification occurs in the active point because of the hydrolysis of metal ion [38][39][40], as explained by Equation (6). If there is no immediate additional supplement of OH โˆ’ from the adjoining solution, this active point will not be repaired (repassivation) and corrosion occurs.…”
Section: Effect Of Aluminate Ionmentioning
confidence: 99%
See 2 more Smart Citations
“…The protection provided by Al(OH) 4 โˆ’ is attributed to its ability to release hydroxyl. In the corrosion process, localized acidification occurs in the active point because of the hydrolysis of metal ion [38][39][40], as explained by Equation (6). If there is no immediate additional supplement of OH โˆ’ from the adjoining solution, this active point will not be repaired (repassivation) and corrosion occurs.…”
Section: Effect Of Aluminate Ionmentioning
confidence: 99%
“…So, in Janotka's work, not only the relatively low alkalinity, but also the sulfate ion present in pore solution were important factors which contributed to depassivation. Cai [6] noticed that tiny corrosion on steel bars may occur, but the development of corrosion can be controlled, because concrete will become more compactness due to the hydration of CSA. Based on the development of the pore solution chemistry studied in Section 3.1, the tiny corrosion at initial stage was probably caused by sulfate ion in the pore solution of low alkalinity.…”
Section: Corrosion Behavior Of Steel In Csa Based Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cai and Zhao [8] compared the protective layer thickness stipulated in the general atmospheric environment of the Chinese and European code for durability of concrete, and concluded that the value stipulated in the European code was 10mm larger than that in China, thus prolonging the carbonization life of the structure for at least 40 years.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sulphoaluminate cement (SAC) is well known for its high early strength, fast setting, and high frost and permeation resistance. The SAC has been widely used in the rapid construction and repair of existing structures [1,2], structures exposed to sub-zero temperature [3], as well as water retaining structures [4,5] in the last few decades. Compared to the ordinary Portland cement (OPC), SAC is green cement with lower CO 2 emissions [6,7,8].…”
Section: Introductionmentioning
confidence: 99%